Cyfrowi komunikatorzy – twórcy czy odtwórcy? - WOBALIS, MIROSŁAW (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Mirosław Wobalis, Digital Communicators – creators or imitators?, Interdisciplinary Contexts of Special Pedagogy, No. 23, Poznań 2018. Pp. 117–133. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.23.07 The article touches upon the issue of influence of modern digital media on the attitudes of recipients/ broadcasters (digital communicators) related to their creative activities. The first indication applies to the fact that the development of digital technologies introduces a new digital order of communication (from the primary order, through the secondary and hybrid order, to the digital order), which in turn provides communicators with a broad spectrum of new methods and tools of communication 0 including tools permitting creative activities. Second of all, it is noted that despite the mentioned rich offer of digital tools and the promotion of creative attitudes, digital media, in particular global social media, are dominated by attitudes of re-production related both to common re-distribution of existing content (sharing, copying and pasting, etc.), and even limiting creativity entirely (likes, tags). The remarks made are compared to opinions of digital media researchers and neurobiologists indicating on the one hand the weakening/ dissolution of the reception of content by digital media (the negative effect of multi-tasking), and on the other hand, the supersaturation of emotions related to the reception of content (negative influence of computer games). In conclusion, attention is turned to the necessity of establishing in contemporary communicators (on all levels of education) of digital communication competences, in particular the promotion of creative attitudes related to these competences.